Fazendas corporativas sojícolas e acumulação de capital no início do século 21: os novos senhores da terra na região do Matopiba - Azerêdo, Raoni Fernandes (2022)
In this thesis, I address the capital accumulation strategies of corporate soy farms located in a vast region of Brazil between the states of Maranhão, Tocantins, Piauí and Bahia, known by the acronym MATOPIBA. These farms have different profiles, origins and economic strategies, but, in common, they implement a system of regional productive monopolization of land. From an original typology derived from qualitative research through interviews, research through bibliography, documents, field research with semi-structured interviews, I defined seven groups of corporate soy farms that have large-scale agricultural production capabilities, with professional management/corporate governance, foreign investments and income capture/land grabbing. In the system implemented, there is the use of methods of land grabbing, which, as a whole, reveal a centralizing and concentrating character of the land market. The corporate farms that make up the seven groups control 3,854,997 hectares in 35 municipalities. I emphasize that the control of land is essential in the strategies of capital accumulation of corporate farms, enabling profit from production and income through patrimonial appreciation. As a trend, they maximize the concept of financialized land rent by correlating investments in stock exchanges and the massive presence of institutional investment funds. I conclude that the seven groups constitute new landlords, by treating land only as a productive-real-estate-financial factor, in close relationship with the transnationalization of capital, promote violence, expropriation and exploitation in Brazilian rural.